Novel One-Pot Synthesis of 2-Substituted 3-Alkoxyisoindolin-1-imine Derivatives from 2-Cyanobenzaldehyde, Amine, and Alcohol - Shen, Sida; Xu, Xingyu; Lei, Min; Hu, Lihong (Synthesis, 2012)
A novel, one-pot procedure has been developed for the synthesis of 2-substituted 3-alkoxyisoindolin-1-imine derivatives via three-component condensation of 2-cyanobenzaldehyde, amine, and alcohol. The efficient and convenient reaction conditions provide the corresponding products from various substrates in good yields (65–96%) catalyzed by acetic acid. The straightforward procedure is a valid contribution to methods for the synthesis of isoindolin-1-imine derivatives.
Keywords: 2-cyanobenzaldehyde; isoindolin-1-imine; multicomponent reaction; 3-alkoxyisoindolin-1-imine